Nature-based Solutions (NbS) for Soil and Water Management - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Inter-American Institute for Cooperation on Agriculture (IICA), 2024)
Guest speaker: Mr. Damian Adjodha - Agroecosystems Director of New-Flower Regenerative Garden (NRG) in St. Lucia